2017
DOI: 10.1038/s41598-017-03410-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Petrolisthes armatus, an invasive species with low dispersal ability

Abstract: Theoretically, species with high population structure are likely to expand their range, because marginal populations are free to adapt to local conditions; however, meta-analyses have found a negative relation between structure and invasiveness. The crab Petrolisthes armatus has a wide native range, which has expanded in the last three decades. We sequenced 1718 bp of mitochondrial DNA from native and recently established populations to determine the population structure of the former and the origin of the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 99 publications
0
14
0
1
Order By: Relevance
“…This is predicted to result in shifts in body size and higher reproductive output, and therefore higher fitness, in the introduced compared to native range 44,45 . Indeed, another invasive porcelain crab, P. armatus, has a smaller size at first reproduction and increased reproductive output in invasive populations on the southeastern coast of the USA compared to native populations in Brazil 46,47 , although it is unlikely that P. armatus on the southeastern coast of the USA came from Brazil 48 . We do not know whether invasive P. elongatus have higher fitness, Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is predicted to result in shifts in body size and higher reproductive output, and therefore higher fitness, in the introduced compared to native range 44,45 . Indeed, another invasive porcelain crab, P. armatus, has a smaller size at first reproduction and increased reproductive output in invasive populations on the southeastern coast of the USA compared to native populations in Brazil 46,47 , although it is unlikely that P. armatus on the southeastern coast of the USA came from Brazil 48 . We do not know whether invasive P. elongatus have higher fitness, Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, in addition to environmental factors that may affect larval survival (e.g., salinity, temperature, food availability), the time required for the development of planktonic decapods is another relevant factor to the invasion of new territories. The dissemination patterns of populations of sessile or sedentary marine organisms are directly related to their dispersal ability [59]. Moreover, decapod crustaceans disperse more commonly during the planktonic larval stages, naturally as well as during invasions.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic and Pacific populations of Cytb, 18S and H3 of four individuals, two from each side of the Panama Isthmus, were newly sequenced. 16S rDNA (GenBank accession numbers , , and ) and COI (GenBank accession numbers , , and ) sequences of the same individuals were taken from a previous study by Hiller and Lessios (). Petrolisthes armatus shows the least transisthmian divergence of all porcellanids sampled to date (Hiller et al, ; Hiller & Lessios, ) and is thus likely to have been separated during the final stages of isthmus completion, 3 Ma (Coates & Obando, ; O'Dea et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…16S rDNA (GenBank accession numbers , , and ) and COI (GenBank accession numbers , , and ) sequences of the same individuals were taken from a previous study by Hiller and Lessios (). Petrolisthes armatus shows the least transisthmian divergence of all porcellanids sampled to date (Hiller et al, ; Hiller & Lessios, ) and is thus likely to have been separated during the final stages of isthmus completion, 3 Ma (Coates & Obando, ; O'Dea et al, ). However, Montes et al () have suggested that after 12.5 Ma only narrow water passages connected the eastern Pacific and the Caribbean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation